Integrated Approaches for the Management of Staple Line Leaks following Sleeve Gastrectomy. (2nd February 2017) - Montuori, Mauro; Benavoli, Domenico; D'Ugo, Stefano; Di Benedetto, Luca; Bianciardi, Emanuela; Gaspari, Achille L.; Gentileschi, Paolo
Abstract : Introduction . Aim of the study was trying to draw a final flow chart for the management of gastric leaks after laparoscopic sleeve gastrectomy, based on the review of our cases over 10 years' experience. Material and Methods . We retrospectively reviewed all patients who underwent LSG as a primary operation at the Bariatric Unit of Tor Vergata University Hospital in Rome from 2007 to 2015. Results . Patients included in the study were 418. There were 6 staple line leaks (1.44%). All patients with diagnosis of a leak were initially discharged home in good clinical conditions and then returned to A&E because of the complication. The mean interval between surgery and readmission for leak was 13, 4 days (range 6–34 days, SD ± 11.85). We recorded one death (16.67%) due to sepsis. The remaining five cases were successfully treated with a mean healing time of the gastric leak of 55, 5 days (range 26–83 days; SD ± 25.44). Conclusion . Choosing the proper treatment depends on clinical stability and on the presence or not of collected abscess. Our treatment protocol showed being associated with low complication rate and minor discomfort to the patients, reducing the need for more invasive procedures.